Penurunan Kadar Besi (Fe) pada Air Sumur dengan Menggunakan Metode Induksi Elektromagnetik (Studi Kasus Talang Jambe) - Ananda, Lutfiah Ananda; Andi Arif Setiawan; Atina (Jurnal Penelitian Fisika dan Terapannya (JUPITER), 2023)
Water is a very important compound for the life of living things including humans for daily needs, one of the sources of water comes from well water. Problems encountered in the well water, including the quality that does not meet quality standards. The water parameters include iron content which according to well water quality standards is 0.3 mg/l. Water quality can be improved by using the electromagnetic induction method. This study aims to analyze the decrease in iron content and dissolved ions due to electromagnetic induction. This research method uses survey and experimental methods. The survey was carried out at Surya Akbar Talang Jambe's residence accompanied by well water sampling and continued with experiments, namely the treatment of the electromagnetic induction method to reduce the levels of iron and dissolved ions. The iron content value of the well water before treatment was 47.85 ppm with 50, 80, and 100 coils and after the treatment the iron content value decreased to 45.79 ppm, 45.62 ppm, and 45.53 ppm, respectively. The parameters of dissolved ions were measured by Electrical Conductivity (EC) meter, the results obtained before treatment were 54.7 S/cm and after induction treatment with 50.80, and 100 turns, each obtained 43 S/cm, 42.8 S/ cm, and 40.6ÂµS/cm.